Teacher, Professional or Both? A Mixed Method Study of the Professional Identity of Vocational Teachers and Trainers in Hungary - Bükki, Eszter; Fehérvári, Anikó (International Journal for Research in Vocational Education and Training, 2024)
Purpose: Vocational educators in many countries enter teaching as a second career and authentic occupational expertise is seen as essential to good quality VET. The changing contexts of VET and the growing diversity of its learning populations also demand the development of teaching expertise. This dual professionalism is related to a unique combination of an occupational and a teacher identity, however, prior, and mainly qualitative research from a limited number of VET contexts suggests that often one side of this duality prevails. Our study aimed to explore the professional identity of vocational educators in Hungary and to identify some of the factors that might influence its formation. Methods: We applied a mixed method design, conducting a teacher survey (N=138) and semi-structured interviews (N=12). The quantitative and qualitative strands followed a parallel design, exploring the same topics but identity views and the organisational context were studied more deeply in the interviews. In the survey, we measured professional identity through a direct question about its type as well as questions about the importance of specific goals and teacher competence areas in vocational teaching. We used statistical and thematic analyses to study our quantitative and qualitative data. Results: Most vocational educators in our study identified as both a teacher and a professional, though the type of identity varied by gender and length of occupational work experience. Perceptions about the main goals in teaching revealed vocation/outcome-focused and student/education-focused goal orientations influenced by gender, qualifications and work experience, while our qualitative data also showed the impact of school culture and the wider socio-economic context. The goal orientations identified in the survey were more balanced for those with a dual identity, and they correlated with perceptions about the importance of different teacher competence areas, which were most influenced by whether or not the educator had obtained a pedagogical qualification. Conclusion: Our findings showed that although most vocational educators also in Hungary claim to have a dual identity, they often prioritise the development of occupational expertise as they believe it is what gives them credibility that is seen as essential to "good VET". Considering the significant impact we have found of teacher education and continued work in the occupation on identity views, it seems of utmost importance that policy and schools recognise and support the development of both occupational and teacher expertise, to ensure a balanced dual identity that seems best suited for vocational teaching.